2005
DOI: 10.1128/iai.73.9.6187-6190.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FimH Adhesins Expressed by Salmonella enterica Serovar Gallinarum Biovars Gallinarum and Pullorum: Reconstitution of Mannose-Binding Properties by Single Amino Acid Substitution

Abstract: Recombinant FimH adhesins of type 1 fimbriae from Salmonella enterica serovar Gallinarum biovars Gallinarum and Pullorum, in contrast to those of Salmonella enterica serovar Typhimurium, did not bind to high-mannose oligosaccharides or to human colon carcinoma HT-29 cells. However, mutated FimH proteins from biovar Gallinarum and biovar Pullorum, in which the isoleucine at position 78 was replaced by the threonine found in S. enterica serovar Typhimurium, bound well to glycoproteins carrying high-mannose oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…Our previous study of FimH sequences from different avian and human isolates of S. Enteritidis revealed that all the analysed isolates express the same allelic variant of FimH (Kisiela et al, 2005b), which was first found in the S. Typhimurium SL1344 strain by Boddicker et al (2002). This strain of S. Typhimurium bound weakly to HEp-2 cells, in contrast to the high-adhesive strain LB5010, which attached strongly to those cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our previous study of FimH sequences from different avian and human isolates of S. Enteritidis revealed that all the analysed isolates express the same allelic variant of FimH (Kisiela et al, 2005b), which was first found in the S. Typhimurium SL1344 strain by Boddicker et al (2002). This strain of S. Typhimurium bound weakly to HEp-2 cells, in contrast to the high-adhesive strain LB5010, which attached strongly to those cells.…”
Section: Discussionmentioning
confidence: 87%
“…They were identified by Western blotting using primary antimyc mAb 9E10 (ATCC, no. CRL-1729) and alkaline phosphataseconjugated goat anti-mouse immunoglobulins (Dako) or rabbit polyclonal antibodies directed against FimH (Kisiela et al, 2005b) and horseradish peroxidase (HRP)-conjugated goat anti-rabbit immunoglobulins (Sigma). The binding of the scFimH proteins to RNase B (Sigma), HRP (Sigma) and mannan-BSA was analysed by far-Western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General suitability of the models is supported by the fact that the threonine residue (Thr-56) that is critical for mannose binding in Salmonella FimH (35) mapped to the top loops of the N-terminal domain exactly where the mannose-binding pocket is predicted to be located. Additional support for the model comes from the similarity of the distribution pattern of binding-enhancing mutations along the tertiary structure of Salmonella FimH with the pattern shown for E. coli FimH.…”
Section: Discussionmentioning
confidence: 99%
“…This designation can be confusing, since naturally occurring mutations resulting in a single-amino-acid substitution in the S. enterica FimH tip adhesin can result in a loss of mannose-sensitive hemagglutination (175). Furthermore, gene clusters encoding type 1 fimbriae of S. enterica and E. coli are both referred to as fim operons, although these are not orthologous gene clusters.…”
Section: The ␥-Fimbriaementioning
confidence: 99%